Levels of satisfaction with current chronic constipation treatment options in Europe – an internet survey. Issue 1 (5th November 2012) - Müller‐Lissner, S.; Tack, J.; Feng, Y.; Schenck, F.; Specht Gryp, R.
Summary Background Data on treatment satisfaction in European men and women with chronic constipation are limited. Aim To assess satisfaction with current treatment among European men and women with chronic constipation. Methods An internet‐based survey was conducted in 2009 in 10 European countries: Austria, Germany, France, Ireland, Italy, Spain, Switzerland, the UK, Belgium and the Netherlands. Participants had self‐reported chronic constipation (<3 bowel movements/week and ≥1 symptoms for ≥6 months of: pain during defecation; lumpy/hard faeces; and feeling of incomplete evacuation). Demographic data and disease history were collected. For participants using laxatives, drug name/class, satisfaction with treatment and interest in other treatments were collected. Results Of the 1941 participants screened, 1355 had chronic constipation and met the inclusion criteria (chronic constipation population). The majority of the chronic constipation population who disclosed their sex (n = 811) were women (82%). Sixty‐eight per cent of respondents (n = 855/1255) reported using laxatives, with the proportion of laxative users differing between subsets. Twenty‐eight per cent (n = 225/793) were (very) satisfied with their treatment, whereas 44% (n = 345/793) were neutral and 28% (n = 223/793) (very) dissatisfied. There was no relationship between type of laxative and degree of (dis)satisfaction. Interest in other treatments was high with 83% (n = 686/827) of respondents 'absolutely' or 'probably' interested. Respondents dissatisfied with their treatment were more likely to be interested in other treatments. Conclusions Laxative‐use is common for chronic constipation. In this large survey, 28% of participants were dissatisfied with their treatment, with the majority interested in other treatments.